DAYA SAING SEKTOR PERTANIAN TANAMAN PANGAN DI PROVINSI BANTEN - Ersarani Putri; Setiawan Sariyoga; Aris Supriyo Wibowo (JURNAL AGRIBISNIS TERPADU, 2019)
In order to maximize the potential of the region's topography and availability of natural resources, it would be wise to map the agriculture market competency to predict successful productivity odds in agriculture to support and help increase the economy in the province. Research to analyze the competitiveness of food crop agriculture sector in district and cities in Banten Province. Using quantitative research with descriptive methods, a study was done in Banten Province analyzing data with a methodology called the agriculture competitive quotient (ACQ). The study done in 2017, calculated that there are different competitive index scores in the district and cities in Banten Province locations. The position of the highest food crop agriculture competitiveness is in Pandeglang District with a competitive index score of 1.16, making Pandegelang District the most competitive in food crop of agriculture in the province. While the position of the highest food crop agriculture competitiveness is in South Tangerang City, with a competitive index score of 0.75, denoting that South Tangerang City does not have a competitive sector yet in food crop agriculture